Faunal Diversity of the Little Rann of Kachchh (LRK), Gujarat, India - Joshi, Jigar D.; Tatu, Ketan; Joshi, Darpak; Kamboj, R. D. (International Journal of Scientific Research in Biological Sciences, 2018)
A study on vertebrate faunal diversity (i.e., diversity of mammals, birds, reptiles and amphibians) of the Little Rann of Kachchh (LRK), Gujarat, India was conducted from October 2015 to March 2017. The Little Rann of Kachchh (LRK) represents a unique ecosystem with combination of saline desert and a vast seasonal wetland. A large portion of the LRK is under legal protection as the Wild Ass Sanctuary (WAS). Islands (locally called bet) are the unique sub ecosystems in the ecosystem of Little Rann of Kachchh. There are around 74 bets and ‘dhasi’ in the LRK. Owing to their relatively better vegetation status, bet’s also support relatively rich fauna. Western, Eastern, Southern and Northern fringe areas of The Rann also have good habitat diversity and hence, they too have good fauna. A total of 260 species of wild vertebrates (i.e., mammals, birds, reptiles and amphibians) were recorded during the present study. They included 26 species of mammals, 210 species of birds, 20 species of reptiles and 4 species of amphibians.